The Whittrick Play of No Nothing: Alan Spence, Edwin Morgan, and Indra’s Net - Kocot, Monika (Text Matters: A Journal of Literature, Theory and Culture, 2018)
The article will attempt a reading of Alan Spence’s play No Nothing (2015). Special attention will be given to the issue of literal and metaphorical space(s), a peculiar, liminal setting of the play, and the ways it determines the flyting between the two characters, two iconic Glaswegians: Edwin Morgan and Jimmy Reid. It seems that in this theatrical space history, politics and poetry inter-are. We may notice how two completely different masters of speech (a poet and a trade union leader) exchange their views on life, how they reflect upon the meaning of their achievements, and how they find a space of convergence in their affirmation of life. As their flyting is “about life, the Universe and everything—from Glasgow to Infinity and beyond,” the article will also address the space of dialogue between Spence’s and Morgan’s poetry. The metaphor of Indra’s net will serve as a useful tool in exploring spatial dimensions of the play and the issue of interconnectedness.